Analysis of Hospital Budget and Operating Costs Study at Pemalang Ashari Hospital - Nurul Mardhiah Sitio; Tri Purwani (Management Dynamics: International Journal of Management and Digital Sciences, 2026)
Covid-19 referral hospitals were studied and it was found that their operational costs had increased. However, their income had actually decreased. This was because there were not many general patients. In addition, asset utilisation was also hampered by the Covid-19 pandemic, which affected the economy. This study sought to find out whether there had been an increase or decrease due to Covid-19. The study used a quantitative method, namely calculating the effectiveness and efficiency ratios. This study uses a descriptive method. The results will be explained in detail. This study compares the conditions before and during Covid-19. The results show that effectiveness in 2019 was 114%. Then, in 2023, it rose to 128%, or an increase of 14%. Meanwhile, efficiency in 2019 was 88%. In 2023, it was 107%. This means there was a decrease of 19%. In conclusion, the budget was well prepared and very effective in 2019 and 2023. However, the use of operational costs during Covid-19 was less efficient. From being quite efficient in 2019, it became inefficient in 2023.